Effect of injury prevention programs that include the Nordic hamstring exercise on hamstring injury rates in soccer players: A systematic review and meta-analysis - Al Attar, W. S. A.; Soomro, N.; Sinclair, P. J.; Pappas, E.; Sanders, R. S. (Sports Medicine, 2017)
Hamstring injuries are among the most common non-contact injuries in sports. The Nordic hamstring (NH) exercise has been shown to decrease risk by increasing eccentric hamstring strength. Objective: The purpose of this systematic review and meta-analysis was to investigate the effectiveness of the injury prevention programs that included the NH exercise on reducing hamstring injury rates while factoring in athlete workload. Methods: Two researchers independently searched for eligible studies using the following databases: the Cochrane Central Register of Controlled Trials via OvidSP, AMED (Allied and Complementary Medicine) via OvidSP, EMBASE, PubMed, MEDLINE, SPORTDiscus, Web of Science, CINAHL and AusSportMed, from inception to December 2015. The keyword domains used during the search were Nordic, hamstring, injury prevention programs, sports and variations of these keywords. The initial search resulted in 3242 articles which were filtered to five articles that met the inclusion criteria. The main inclusion criteria were randomized controlled trials or interventional studies on use of an injury prevention program that included the NH exercise while the primary outcome was hamstring injury rate. Extracted data were subjected to meta-analysis using a random effects model. Results: The pooled results based on total injuries per 1000 h of exposure showed that programs that included the NH exercise had a statistically significant reduction in hamstring injury risk ratio [IRR] of 0.490 (95 % confidence interval [CI] 0.291-0.827, p = 0.008). Teams using injury prevention programs that included the NH exercise reduced hamstring injury rates up to 51 % in the long term compared with the teams that did not use any injury prevention measures. Conclusions: This systematic review and meta-analysis demonstrates that injury prevention programs that include NH exercises decrease the risk of hamstring injuries among soccer players.